IMPLEMENTATION OF CONTROL POLICY OF DIPHTHERIA OUTBREAK AND OUTBREAK RESPONSE IMMUNIZATION (ORI) IN KOTA DEPOK, 2017 - Sari, Dian Novita; Achadi, Anhari (UI Scholars Hub, 2019)
Diphtheria is a contributor to an outbreak (KLB) for some regions in Indonesia, included West Java Province. Diphtheria cases had increased through 2015 - 2016, the cases increased from 59 cases to 153 cases. Depok City became one of the contributors of diphtheria cases that have fluctuating incidents. Disease trends have decreased in 2013-2015 but then increased in 2016 to 8 cases. This study discusses policy implementation, viewed from policy sources, resource arrangements, the characteristics of implementing agencies, bureaucratic structures, communications, the influence of dispositions and socio-economic and political circumstances in control of Diphtheria Outbreak and Outbreak Response Immunization (ORI) in Depok City in 2017. This type of research is qualitative research with descriptive design, through in-depth interviews and document review. The results showed that the limited resources, especially human resources, the lack of cross-sectoral concern and social environment factors, including the rejection of some community for vaccination, became a challenge in controlling the Diphtheria Outbreak and Outbreak Response Immunization (ORI) in Depok City. It is expected that policy implementers can commit to working together, and taking into the influential factors in policy implementation, as well as government support in providing halal and safe vaccines and research on bioterrorism can also be done as solving cases of diphtheria fluctuating annually.